Visual Programming for Teaching Geometry in Architectural Education - Herrera, Pablo C. (2023)
Mathematicians and computational designers from a School of Architecture, explore visual programming in the environment of a design software with exercises of a basic mathematics course to overcome the limitations of hand drawing and computerized representation of geometry. We link the learning of geometry, which was associated with abstract aspects of mathematics, with the possibilities of solving design problems in the same environment that students use to design with technologies. Visual programming allowed to create and reuse formulas that modeled variations of different exercises, preparing the model for visualization and digital fabrication with 3D printing and laser cutting. This research promotes a learning experience using algorithms and personalized computer graphics throughout design learning and to value the use of mathematics to explore geometric possibilities in design problems.